Labour code (Government Printing Office St. George'sGD, 2000)
Contains the Employment Act, 1999; the Labour Relations Act, 1999; the Empl;oyment (Amendment) 1999 (Act No.10of 2000); the Labour Relations (Amendment) 1999 (Act No, 11 of 2000); the Employment Act 1999 (Appointed Day) Proclamation (S.R. & O, No. 10 of 1999); and, the Labour Relations Act, 1999 (Appointed Day) Proclamation (S.R. & O. No. 11 of 1999)
Keywords: LABOUR CODE